The pro-angiogenic role of hypoxia inducible factor stabilizer FG-4592 and its application in an in vivo tissue engineering chamber model - Zhou, Muran; Hou, Jinfei; Li, Yuan; Mou, Shan; Wang, Zhenxing; Horch, Raymund E.; Sun, Jiaming; Yuan, Quan (Scientific Reports, 2019)
Tissue engineering is a promising technology used as an alternative to organ/tissue transplantation which is often limited by donor shortage. The construction of large-sized engineered tissue requires a fast and sufficient vascularization process. Previous studies have shown that hypoxia- inducible factor (HIF)-1 alpha may promote the vascularization process implying that stabilized HIF-1 alpha can be applied in the engineering of large-sized tissue. However, the toxicity and off-target effect of previously reported HIF-1 alpha stabilizers limit their clinical application. FG-4592, a small molecule specific HIF stabilizer, was previously investigated as an anti-anemia drug in a phase-III clinical trial. Here we found that FG-4592 promoted tube formation in an in vitro model of angiogenesis by stabilizing HIF-1 alpha and activating vascular endothelial growth factor (VEGF). When FG-4592 immobilized fibrin gel scaffold was implanted into a subcutaneous tissue engineering chamber, the vascularization process was significantly enhanced through the similar mechanisms which was verified in vitro. We conclude that FG-4592 may serve as a pro-angiogenic molecule for the construction of large-sized engineered tissue where intensive angiogenesis is required.
CRIS-Team WoS Importer:2019-04-30